Biodiversity of nekton in Batangtoru River and its tributaries in North Sumatra, Indonesia - Desrita Desrita; AHMAD MUHTADI; RUSDI LEIDONALD; RINA D’RITA SIBAGARIANG; NURFADILLAH (Society for Indonesian Biodiversity, 2020)
Abstract. Desrita, Muhtadi A, Leidonald R, Sibagaring RD, Nurfadillah 2020. Biodiversity of nekton in Batangtoru River and its tributaries in North Sumatra, Indonesia. Biodiversitas 21: 2344-2352. Batangtoru River which flows from the Tapanuli highlands (i.e., Sipirok, Tarutung, Siborong-borong, and Silangit) to the southwestern Indian Ocean is an important habitat for aquatic organisms in the western region of North Sumatra. This research was done to provide basic data on biodiversity of aquatic organisms in Indonesia, especially North Sumatra. The study was conducted in July-August 2019. Nekton was captured using backpack electrofishing units (12 volts and 9 Amperes), traps, nets, and bamboo trap. This study found 68 nekton species, consisting of fish (57 species), crab (3), shrimp (6), lobster (1), and 1 freshwater turtle (1). In general, nekton found in the Batangtoru River and its tributaries are native and economically valuable fish (Tor and eel), including the newly discovered species, which was, Hemibagrus caveatus. Invasive fish found consisted of 6 species, i.e., Cyprinus carpio, Oreochromis mossambicus, Oreochromis niloticus, Xiphophorus helleri, Hypostomus plecostomus, and Trichogaster pectoralis. The only invasive crustacean found was freshwater crayfish (Cherax quadricarinatus).